Critical Thinking Skills Incorporated in Self-Learning Curriculum for Kindergartens - Bahatheq, Rajaa (Advances in Social Sciences Research Journal, 2019)
The educational curriculum seeks to develop the different types of thinking among students of both genders. The current research aims to finding out the inclusion of critical thinking skills' extent in the teacher's parameter guide questions and activities of the self-learning in Riyadh Kindergartens and educational units. This research adopts the descriptive analytical curriculum; through educational units' lessons analysis, in terms of self-learning, duplications measurement and percentages of employing the critical thinking skills. The foregoing duplicates showed that the self-learning curriculum units do support the induction skills in relevant units (national, food, housing), observation skill (family, book, clothes), while it does not support credibility and conclusion skills, further the assumption skill scored weak rate in all units.